Vegetative Growth Response of Corn (Zea mays) Against Actinomycetes, Azospirillum, and Azotobacter from the Rhizosphere Neem (Azadirachta indica) - Yusminah Hala; A.Irma Suryani; Octavia Cisiliana Devi (bionature, 2023)
This research is an experimental study that aims to determine the effect of the application of N2-fixing bacteria Actinomycetes, Azospirillum, and Azotobacter on the vegetative growth parameters of corn plants and on the nitrogen content of corn plants. Parameters for measuring the growth of corn plants include: formation rate of radicle length, plant height, number of leaves, leaf length, fresh weight of plants, fresh weight of plant roots, dry weight of plants, dry weight of plant roots, total N content in plants, as well as physical and chemical qualities of the ground. Experiments on the application of N2 -fixing bacteria on corn plants on a laboratory scale were carried out to determine the in vitro effect of microbes on corn seeds. The pot test was carried out to determine the effect of N2-fixing bacteria on the vegetative growth of corn plants in vivo. Data were analyzed using ANOVA with Duncan's test. The results showed that corn plants inoculated with Actinomycetes, Azospirillum and Azotobacter showed a significant different growth from corn plants without nitrogen fixing bacteria, namely formation rate of radicle length, plant height, number of leaves, leaf length, fresh weight, dry weight, total N content (%) of crops, and soil physical and chemical quality. It can be concluded that the inoculation of nitrogen-fixing bacteria in corn plants has a significant effect on plant vegetative growth parameters and plant nitrogen content.Keywords: Nitrogen fixing bacteria, Actinomycetes, Azospirillum, Azotobacter, Plant vegetative growth.